2023
DOI: 10.3390/ijerph20064970
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Temperature on 24-Hour Movement Behaviors among Chinese Freshmen Students

Abstract: Background: Human populations worldwide have experienced substantial climate change issues. Gaps in scientific literature remain regarding the relationship between temperature and 24-hour movement behavior among people. The purpose of this study is to examine the impact of temperature on 24-hour movement behavior including physical activity (PA), sedentary behavior (SB) and sleep duration among university students living in Beijing, China. Methods: We conducted follow-up health surveys on 44,693 freshmen stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Using accelerometers to measure PA, 3 regional studies found that the proportion of children and adolescents in Tianjin was 1.2% [8], 1.0% in Hong Kong [9], and 22.6% in Shanghai. In addition, 5 other studies using questionnaires found that the proportion in China averaged 0.3-7% [10][11][12][13]. Due to the limitations of sample representativeness (regional samples) or research methods (questionnaire surveys), the above data cannot comprehensively and objectively reflect the compliance with the 24-Hour Movement Guidelines in Chinese children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using accelerometers to measure PA, 3 regional studies found that the proportion of children and adolescents in Tianjin was 1.2% [8], 1.0% in Hong Kong [9], and 22.6% in Shanghai. In addition, 5 other studies using questionnaires found that the proportion in China averaged 0.3-7% [10][11][12][13]. Due to the limitations of sample representativeness (regional samples) or research methods (questionnaire surveys), the above data cannot comprehensively and objectively reflect the compliance with the 24-Hour Movement Guidelines in Chinese children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few relevant studies in the Chinese Mainland, and the conclusions are inconsistent. Wang et al [12] found that meeting the overall 24-Hour Movement Guidelines is not associated with overweight and obesity but that adequate SLP can help reduce the rate of overweight and obesity in children and adolescents. Chen et al [10] showed a different finding in their study, which indicated that children and adolescents who met the overall 24-Hour Movement Guidelines or a combination of the MVPA and SLP guidelines had a lower rate of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation